Os corpos de bombeiros militares emancipados das polícias militares : prospecção e análise dos parâmetros norteadores do seu 'desenho' organizacional - Costa, Carlos Marcelo d'Isep (2002)
After the promulgation of Brazil's Federal Constitution in 1998, the firemen of Brazil started to emancipate from the military police. This study, taking as reference the sprouting of these 'new organizations', attempted to analyze the performance of the guiding parameters of their organizational structure, and at the same time, seeks to promote in its managers the study of the subject of 'Organizational Change'. The research contemplated five of a total of nineteen emancipated military fire departments to directly put in focus the study's central questiono Parallel to the central question the study raised data about ali fire departments with the purpose of showing their organization in more general aspects. The inquiry was exploratory and explanatory conducted by field, bibliographical and documentary research. The data was collected by interviewing officers (colonels, lieutenant-colonels and majors) of the fire departments and by consultation of legal devices. The results revealed, in a general way, that the guiding parameters of the organizational structure present some problems. The analyses of the problems lead to conclusion that they can be solved by means of managerial actions and change of the organizational culture.